(untitled) (Global Business Management Review (GBMR), 2024)
Although numerous equity risk premium estimates have been published using various estimation methods, especially in advanced economies, the accuracy of these estimations and which estimation method is the most appropriate remain inconclusive. There is, however, limited studies in emerging markets. This paper aims to bridge this gap by evaluating the associations among equity risk premium models for a small emerging market, i.e., Malaysia. This descriptive research adopts five methods to derive the risk premiums from 2005 to 2022, where the historical premiums are estimated using two averaging methods, i.e., arithmetic and geometric average, while the implied premiums are estimated using three methods. The first two implied premium methods are based on the constant growth dividend discount model, in which the first model uses the historical dividend growth, while the second applies the earnings retention model. The third is the yield-gap method. The findings demonstrate a wide disparity between arithmetic and geometric average historical premiums. The historical premiums are also highly volatile than the implied premiums, which is a common observation in emerging markets. Moreover, the historical premiums are very sensitive to financial or economic crises. Interestingly, the implied premiums appear to be exhibiting a mean reversion tendency since the global financial crisis, where the mean values ranged between 7.02 and 8.64 percent over time. The results may benefit policymakers, firms and investors in formulating accurate financing and capital budgeting decisions. The findings also contribute to the asset pricing literature by furnishing new evidence in a small emerging market context.